Antiepidermal Growth Factor Receptor Therapy in Squamous Cell Carcinoma of the Head and Neck. (19th June 2012) - Shaib, Walid; Kono, Scott; Saba, Nabil
Abstract : Squamous cell carcinoma of head and neck (SCCHN) is the most common neoplasm of the upper aerodigestive tract. In this paper, we attempt to summarize the role and applications of the epidermal growth factor receptor (EGFR) inhibitors monoclonal antibodies (moAbs) and tyrosine kinase inhibitors (TKIs) locally advanced as well as metastatic SCCHN. Targeted therapy in SCCHN is now incorporated in the first-line regimes for advanced disease. Novel targeted agents, including the EGFR antibody, cetuximab, have been approved for use as single agents or in combination with radiation therapy or chemotherapy in treatment of recurrent metastatic or locally advanced SCCHN. Refractory mechanisms that bypass the pathway of EGFR inhibitors activity are identified explaining resistance to targeted therapy. Strategies of cotargeting EGFR and other pathways are under investigation. Examples of targeted therapy being used include mammalian target of rapamycin (mtor) inhibitors, antivascular endothelial growth factor (VEGF) moAb, and other inhibitors. We will be focusing our paper on the preclinical and clinical aspects of EGFR inhibition in SCCHN and touch upon other targeted therapies in application.